Local perspectives of forest landscapes: A preliminary evaluation of land and soils, and their importance in Malinau, East Kalimantan, Indonesia - Basuki, I.; Sheil, Douglas (Center for International Forestry Research, 2005)
All too often communities and their natural environments are the victims of poorly informed decisions. Those coming from outside often have little understanding of how local people perceive and prioritize the natural resources they depend on. The enormous harm poorly informed decisions can inflict on both people and the environment can and must be avoided. The research evaluates the relationship between the people of the forest rich Malinau river valley of East Kalimantan and the condition of local land resources. Its central aim is to clarify local peoples’ views and knowledge about their land resources and to suggest promising land-use choices. the authors worked with seven communities in implementing a variety of natural resource research activities. This report focuses on results from the land and soils aspects of these surveys. It considers a range of important questions and issues, including: The nature of land and soil conditions in the upper Malinau Watershed; How local people perceive and use this landscape; How local views regarding cultivation choices differ from technical evaluations; Best land-use options